Studi Eksperimen Metode Pembelajaran Role Play Dan Story Telling Berbantuan Video Terhadap Keterampilan Motivasi Belajar - Jumiati Siska (Journal Of Dehasen Educational Review, 2025)
This experimental study was carried out at MTSN 2 dan MTSN 1. The population of this research is the students of the eighth grade in Kecamatan Kota in Benteng, Central Java in academic year 2020/2021. This research used cluster random sampling in taking the sample. The two instruments were tried out to get validity and reability for the quetionnaire and readability percentage for speaking test. Then the data was analyzed by using multifactorial analysis of variance ANOVA 2x2 and Tukey test. Before conducting the ANOVA test, normality and homogeneity test were conducted. After the data were analyzed, the findings are as follow: (1) There is difference of speaking skill achievement between the students taught by Role Play and those by Story Telling, Fvalue = 51,512 > Ftabel 4,027. The students who taught by using Role Play have better achievement. (2) There is influence difference between the students who have high motivation and those who have low motivation, Fvalue = 5,345 > Ftabel = 4,027. The students with high motivation have better achievement. (3) There is influence interaction between Role Play and Story Telling related to motivation, Fvalue = 7,952 > Ftabel = 4.027.